2016
DOI: 10.3109/09638288.2015.1107773
|View full text |Cite
|
Sign up to set email alerts
|

Peer mentoring of adults with spinal cord injury: a transformational leadership perspective

Abstract: Displays of transformational leadership by peer mentors (i.e. transformational mentoring) were reported by mentees to be associated with a range of adaptive psychological and behavioural outcomes. The results have the potential to inform the development and dissemination of peer mentor-based interventions and initiatives. Implications for Rehabilitation Within the context of spinal cord injury (SCI) rehabilitation, positive peer mentorship is reflected in mentors' use of transformational leadership behaviours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 24 publications
(32 reference statements)
3
35
0
Order By: Relevance
“…Finally, this study adds to the research on the importance of peer groups and peer support for patients and family members engaged in SCI care and rehabilitation [48,49]. Throughout the focus groups, caregivers were able to not only express their needs in their own words, but they were able to interact and share their experiences with one another.…”
Section: Discussionmentioning
confidence: 92%
“…Finally, this study adds to the research on the importance of peer groups and peer support for patients and family members engaged in SCI care and rehabilitation [48,49]. Throughout the focus groups, caregivers were able to not only express their needs in their own words, but they were able to interact and share their experiences with one another.…”
Section: Discussionmentioning
confidence: 92%
“…5; 27 Other peer mentorship studies have also discussed the importance of relatedness. 11 These findings therefore highlight that if mentors can enhance the psychological needs of competence and relatedness among their mentees, the mentees will likely report greater QoL and specific types of participation. On a practical level, mentors should continue (or start) providing positive feedback, demonstrating new skills, and structuring their mentorship sessions (e.g., outlining goals and expectations of the sessions) to enhance competence.…”
Section: Spinal Cord Injury Peer Mentorship 13mentioning
confidence: 90%
“…Identifying these topics can help prioritize information to be taught in community-based mentorship training programs. Third, whereas mentoring relationships initiated in hospital settings may last from 1 month to 5 years or longer [3,8,10], most mentors in our study reported no further communication with mentees after 4 months. Collecting the reasons for terminating communication (e.g., resolution of the issue for which mentorship was sought, the quality of the match, mentor availability) could improve the design and implementation of mentorship programs.…”
Section: Discussionmentioning
confidence: 63%
“…People who receive SCI peer mentorship (i.e., mentees) report various physical, social and psychological benefits of the mentorship [4][5][6][7]. Although little is known about how to maximize these benefits, recent research suggests a linkage between SCI peer mentors' displays of transformational leadership (TFL) and positive outcomes in their mentees [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation